The Influence of E-Service Quality and Food Quality on Behavioral Intention through Attitude: Study on Millennial Moms as Online Grocery Shoppers in West Java - Desy Oktaviani (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
This study aims to examine the effect of e-service quality and food quality on behavioral intention through attitude among millennial moms as online grocery shoppers in West Java, Indonesia. Purposive sampling was used to obtain a sample of 298 respondents who met the research criteria. SEM-PLS testing was used to analyze the data. What was found in the course of the work? This will refer to analysis, discussion, or results. The results of this study indicate that the e-service quality and food quality variables have a significant positive influence on attitude. Additionally, attitude was found to have a significant positive effect on behavioral intention also playing a role as mediator. This study specifically examines the behavior of millennial mothers in West Java, with data collection conducted immediately after the pandemic period. Differences in behavior are highly likely to be found when research is conducted subsequently. The findings of this study can provide valuable insights into the influence of e-service quality and food quality on behavioral intention in the Indonesian online grocery industry specifically for West Java Market. It offers companies a deeper understanding of consumer behavior and the crucial factors that drive long-term decision-making in online grocery services. This study presents a unique perspective by examining the impact of the post-pandemic digitalization trend on online grocery shopping. The special emphasis lies in the researcher's ability to provide insights into post-pandemic behavioral changes, positioning the pandemic as a catalyst for shifts in digitalization trends. In contrast to other studies focusing on behavioral aspects during the pandemic, this research sheds light on behavior after the pandemic.